(untitled) (Journal of Economic Research & Business Administration, 2016)
The majority of single-industry towns depend on the main enterprises in towns that define the basic functionality of the town. By the amend-ment, the article discussed the socio-economic problems of formation of small and single-industry towns; investigated and substantiated scientific and theoretical basis of improving the management of socio-economic de-velopment of towns.